2019
DOI: 10.3390/medicina55050158
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) Cut-Offs: A Cross-Sectional Study in the Czech Population

Abstract: Background and Objectives: The key pathogenetic mechanism of glucose metabolism disorders, insulin resistance (IR), can be assessed using the Homeostasis Model Assessment of IR (HOMA-IR). However, its application in clinical practice is limited due to the absence of cut-offs. In this study, we aimed to define the cut-offs for the Czech population. Methods: After undergoing anthropometric and biochemical studies, the sample of 3539 individuals was divided into either nondiabetics, including both subjects with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 21 publications
2
33
0
2
Order By: Relevance
“…Although IR is usually defined as a value greater than the 75th percentile value for non-diabetic subjects, the cut-off values reported in the literature vary widely [61]. The results from the present study are very similar to those reported in a study defining HOMA-IR cut-offs for middle-aged men and women in the Czech Republic [62]. In a crosssectional study of Chinese people, Lee et al [63] derived an optimal HOMA-IR cut-off of 2.0 to discriminate nondiabetics from diabetics.…”
Section: Discussionsupporting
confidence: 86%
“…Although IR is usually defined as a value greater than the 75th percentile value for non-diabetic subjects, the cut-off values reported in the literature vary widely [61]. The results from the present study are very similar to those reported in a study defining HOMA-IR cut-offs for middle-aged men and women in the Czech Republic [62]. In a crosssectional study of Chinese people, Lee et al [63] derived an optimal HOMA-IR cut-off of 2.0 to discriminate nondiabetics from diabetics.…”
Section: Discussionsupporting
confidence: 86%
“…However, the mean level of insulin (9.1 mIU/l) is similar to that in the group with a C-peptide range of 711-950 pmol/l (9.00 mIU/l). Similarly, the range of BMI values seems to be wider (from 28.3 to 37.4 kg/m 2 ) but approaching that in Czech patients without diabetes in the year 2018 (from 32.8 to 33.3 kg/m 2 ) (Horáková et al, 2019). Andrade et al (2018) also came to similar conclusions regarding glycaemia changes in healthy individuals divided by the quartiles of C-peptide.…”
Section: Discussionmentioning
confidence: 57%
“…Insulin resistance was assessed by the HOMA IR score (Homeostasis Model Assessment for Insulin Resistance) based on insulin and glucose concentrations. HOMA IR cut-off was set at 3.63, considered a signal of glucose metabolism alterations within the Czech population (Horáková et al, 2019). A body mass index (BMI) reference range of 20.0-24.9 kg/m 2 (normal weight) was calculated by Svačina and Bretšnajdrová (2003).…”
Section: Methodsmentioning
confidence: 99%
“…The serum insulin, ghrelin, and leptin concentrations were measured with ELISA kits (EZRMI-13K and EZRL-83K, Millipore Corporation, Burlington, MA, USA; EZRGRT-91K, Linco Research, St Charles, MO, USA). The homeostatic model assessment for insulin resistance (HOMA-IR) and the quantitative insulin sensitivity check index (QUICKI) were calculated in accordance with the standard formulas from fasting plasma glucose and insulin [ 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%